1996
DOI: 10.1577/1548-8640(1996)058<0187:eodswl>2.3.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Diets Supplemented with Live Food on the Foraging Behavior of Cultured Fall Chinook Salmon

Abstract: The use of diets supplemented with live food lo increase the postrelease foraging ability of hatchery-reared fall chinook salmon Oncorhynchus tshawytscha was investigated. Replicate groups of fry were reared in six 2.4-m-diarneter circular tanks and fed one of two diets. Fish in three tanks received a commercially available pelletized diet; fish in the other three tanks were given the opportunity to forage on natural live prey (mysids, mosquito larvae, chironomid larvae, and daphnia) prior lo their daily ratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
40
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(41 citation statements)
references
References 12 publications
1
40
0
Order By: Relevance
“…Consequently, releasing fish during a period of compensatory growth may counter the otherwise beneficial effects that variable food regime and environmental enrichment may provide. Previously it has been suggested that providing a diet that reflects naturally occurring food would be one way to improve survival in hatchery-reared fish (Maynard et al 1996). But the reality is that such an approach will be impossible for large-scale production of fish, because rearing sufficient quantities of live invertebrate prey is too costly and too labour intensive.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, releasing fish during a period of compensatory growth may counter the otherwise beneficial effects that variable food regime and environmental enrichment may provide. Previously it has been suggested that providing a diet that reflects naturally occurring food would be one way to improve survival in hatchery-reared fish (Maynard et al 1996). But the reality is that such an approach will be impossible for large-scale production of fish, because rearing sufficient quantities of live invertebrate prey is too costly and too labour intensive.…”
Section: Discussionmentioning
confidence: 99%
“…The success of conservation programs that use hatchery steelhead can hinge upon fish successfully feeding after release (Massee et al 2007). The condition of most hatchery salmonids have been shown to deteriorate after release, and may be accompanied by acute post-release mortality (Miller 1952;Vincent 1960;Reimers 1963;Suboski and Templeton 1989) due to an inability to recognize available food (Sosiak et al 1979;Maynard et al 1996;Massee et al 2007), decreases in foraging time (Bachman 1984), and poor feeding efficiency (Ersbak and Haase 1983;Maynard Factor Sum of squares . 1996;Sundstrom and Johnsson 2001).…”
Section: Discussionmentioning
confidence: 99%
“…An impending study is to test the differences in these physiological parameters between hatchery and wild fish. Additionally, Maynard et al (1996) reported that diets supplemented with aquatic insects can increase the post-release foraging effectiveness of hatchery chinook salmon (O. tshawytscha). Olla and Davis (1989) found that learning predation and not being handled enhanced predator avoidance in hatchery coho salmon.…”
Section: -2 Perspectives For Studies On the Improvement Of Seed Promentioning
confidence: 99%